RANCANG BANGUN ALAT PENGUKUR TINGKAT STRES MENGGUNAKAN METODE FUZZY LOGIC - Hadya, Pradhipta Kresna; Rasmana, Susijanto Tri; Wibowo, Madha Christian (Journal of Control and Network Systems, 2015)
Stress level measurement using fuzzy logic method is a tool used to measure the level of stress with the parameters of heart rate, body temperature, and blood pressure. Using Arduino Uno R3 as data processor, DS18B20 as the temperature sensor, MPX5050DP as heart rate and blood pressure sensor. The results of the measured parameters are then compared with stress levels table by using fuzzy method as decision makers. Body temperatue measurement using DS18B20 has 99,48 % accuracy rate, while systole blood pressure, diastole blood pressure and heart rate measurements have Â 91,94 %, 89,59 % and 96,7 % accuracy rate. This system works very well in measuring the level of stress, and the fuzzy system works as expected.